A case series on bullous pemphigoid like scabies: A diagnostic challenge (Indian Journal of Case Reports, 2022)
Scabies is an ectoparasitic infection caused by Sarcoptes scabiei var. hominis in humans. Accurate figures of the prevalence of scabies are difficult to obtain, it seems to affect around 100–300 million people worldwide. Scabies is usually transmitted by close intimate physical contacts, such as the sharing of a bed or prolonged hand-holding. Scabies mites survive for 24–36 h outside of human bodies. Itching is the most obvious manifestation of scabies, which is usually sparing the face in adult classic scabies. The onset occurs 3–4 weeks after acquiring the infection. Bullous pemphigoid-like scabies is one of the atypical and rare forms of scabies that may be overlooked and mismanaged, where only 44 cases worldwide with this mode of presentation were reported. Here, we reported a series of three cases of bullous pemphigoid-like scabies, which presented with nocturnal itching and vesiculobullous lesions that are to the best of our knowledge the first cases reported in our country